Couple Construction Model as an Alternative of Improvement Method Due to Failure and Defect of Cohesion Parameter (C) - Mustaffa Anjang Ahmad; Putera Agung Maha Agung; Yuwono Yuwono; Saiful Azhar Ahmad Tajudin (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
Road or highway system as an important part for development infrastructure program is a very critical and crucial problem for increasing the people's economic resources. Traffic of people and goods would have some disturbances if the road service damaged. One of main problems out of order the road is a groundwater movement in uncontrolled condition at study area. Therefore, a method of ground improvement has to be implemented at the road margin area. This study is going to focus on a couple model of construction systems implemented to avoid all slope sliding factors. From some laboratory and field data observations, clay layers as soil foundation during the road life time service plan at the study site indicated that there were some reductions of soil shear strength due to cohesion (c) values decreased. Fast alteration of water content (w) was the main cause of failure and defect of cohesion parameter, especially for expansive soil layers. From stability analysis using some geotechnical data and calculated by PLAXIS application software, the existing slope sliding was found in unsafe condition with safety factor (SF) ≤ 1.25. However, one option of design criteria using a couple construction model was obtained the better of safety factor with (SF) > 1.25.